Neurotransmitter Mechanisms Underlying Sacral Neuromodulation of Bladder Overactivity in Cats - Bandari, Jathin (Neuromodulation, 2016)
OBJECTIVE: To determine the role of opioid, β-adrenergic, and metabotropic glutamate 5 receptors in sacral neuromodulation of bladder overactivity. MATERIAL AND METHODS: In α-chloralose anesthetized cats, intravesical infusion of 0.5% acetic acid (AA) irritated the bladder and induced bladder overactivity. Electric stimulation (5 Hz, 0.2 ms, 0.16–0.7V) of S1 or S2 sacral dorsal roots inhibited the bladder overactivity. Naloxone, propranolol, or MTEP were given intravenously (i.v.) to determine different neurotransmitter mechanisms. RESULTS: AA significantly (p <0.05) reduced bladder capacity to 7.7 ± 3.3 mL from 12.0 ± 5.0 mL measured during saline infusion. S1 or S2 stimulation at motor threshold intensity significantly (p <0.05) increased bladder capacity to 179.4 ± 20.0% or 219.1 ± 23.0% of AA control, respectively. Naloxone (1 mg/kg) significantly (p <0.001) reduced the control capacity to 38.3 ± 7.3% and the bladder capacity measured during S1 stimulation to 106.2 ± 20.8% of AA control, but did not significantly change the bladder capacity measured during S2 stimulation. Propranolol (3 mg/kg) significantly (p <0.01) reduced bladder capacity from 251.8 ± 32.2% to 210.9 ± 33.3% during S2 stimulation, but had no effect during S1 stimulation. A similar propranolol effect also was observed in naloxone-pretreated cats. In propranolol-pretreated cats during S1 or S2 stimulation, MTEP (3 mg/kg) significantly (p <0.05) reduced bladder capacity and naloxone (1 mg/kg) following MTEP treatment further reduced bladder capacity. However, a significant inhibition could still be induced by S1 or S2 stimulation after all three drugs were administered. CONCLUSIONS: Neurotransmitter mechanisms in addition to those activating opioid, β-adrenergic, and metabotropic glutamate 5 receptors also are involved in sacral neuromodulation.